ANAK YANG DILACURKAN; LATAR BELAKANG DAN PERMASAHANNYA Studi Kasus di Kota Surabaya - Yanuar Farida Wismayanti (Puslitbangkesos Kementerian Sosial RI, 2009)
Exploitation sexual for children is the big issues about child protection. This paper described, the background this condition are poverty, less of education, deception, lifestyles, patriarchi culture and frustration. Exploitation sexual for children has many problems. Trafficking brings the bad effects for women and children, many things that bring them to the worst and unbeneficial condition, whether in social, psychological, or the children growth and their social interaction process. They are sensitive with victime from their pimp, customer, or their boyfriend. The other problem, they are very sensitive infected sexual infection, including HIV/AIDS. To protect the children, some institute care of children, maked the programsprevention, like supporting group, theater, media campaign (poster, stickers, leaf leat), and awareness about the risk from their sexual activiti;.